Entrepreneurship development in Nigeria: a case of micro and small enterprises in Kano state - Abubakar, Salisu Garba (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Entrepreneurship has become a veritable tool for economic development. It plays a crucial role in creating jobs, reducing poverty, increasing competition and promoting innovations. Nigeria is endowed with abundant human and material resources that can be used to build a strong, virile and prosperous economy. There are bountiful opportunities for entrepreneurship development especially through micro and small business activities. But unfortunately entrepreneurship development has been marred with series of problems. There are several factors militating against entrepreneurial activities which include lack of accessibility for finance for business start up, inadequate managerial and technical knowledge for sustaining the business, weak and inadequate infrastructural facilities, lack of government support and inconsistency of policies for entrepreneurial development. Therefore, the objective of this study is to identify and examine factors influencing entrepreneurship development at both individual and aggregate levels in Nigeria.